Harvard business review on increasing customer loyalty (Harvard business review paperback series, 2011)
How do you keep your customers coming back - and get them to bring others? This collection of HBR articles helps you: turn angry customers into loyal advocates; get more people to recommend you; boost customer satisfaction by satisfying your employees; and, focus on profitable customers - whether they're loyal or not